2022
DOI: 10.1038/s41467-022-33613-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of EntV reveals a 12 amino acid fragment protective against fungal infections

Abstract: Fungal pathogens are a continuing challenge due to few effective antifungals and a rise in resistance. In previous work, we described the inhibition of Candida albicans virulence following exposure to the 68 amino acid bacteriocin, EntV, secreted by Enterococcus faecalis. Here, to optimize EntV as a potential therapeutic and better understand its antifungal features, an X-ray structure is obtained. The structure consists of six alpha helices enclosing a seventh 16 amino acid helix (α7). The individual helices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…Interestingly, it has been reported that the bacteriocin enterocin O16 is an E. faecalis virulence factor in Drosophila ( 33 ). Enterocin O16 is also known as EntV, which is heat resistant and able to kill some lactobacilli strain as well as to inhibit the hyphal growth, the virulence, and the biofilm formation of Candida albicans ( 34 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it has been reported that the bacteriocin enterocin O16 is an E. faecalis virulence factor in Drosophila ( 33 ). Enterocin O16 is also known as EntV, which is heat resistant and able to kill some lactobacilli strain as well as to inhibit the hyphal growth, the virulence, and the biofilm formation of Candida albicans ( 34 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…The active form of EntV is 68 amino acids [ 60 ], which per se does not exhibit antifungal activity, inhibits C. albicans biofilm formation both in vitro and in vivo [ 61 ]. In a recent study aimed at optimizing its potential anti- Candida therapeutic the authors identified a shorter 12-mer peptide derived from EntV which maintained the inhibitory activity, including against Candida biofilms [ 62 ].…”
Section: The Futurementioning
confidence: 99%
“…In addition, the role of antimicrobial peptides (AMPs) in treating IFDs have been well investigated; for example, peptides HIF-1α and LL-37 can inhibit C . albicans colonization [ 20 ]. Overall, these advances in fungal immunotherapies hold great promise for improving the treatment of fungal infections, especially in patients with weakened immune systems.…”
Section: Antifungal Immunotherapy In Invasive Fungal Infectionmentioning
confidence: 99%